Analisis Analisis Pengaruh Pariwisata Terhadap Pendapatan Asli Daerah Di Kabupaten Gresik: pengaruh pariwisata terhadap pendapatan asli daerah - Dandi Muhammad Ridho Dandi (JEBIM Prima, 2023)
Tourism is one of the activities that generates the biggest profits or dividends for a country or region. This can be seen from several sectors that have a major influence on local revenue. In this study the authors used quantitative data obtained from institutions related to this research. The variables used by this writer are the number of tourists, the number of hotels, the number of restaurants, and the total income of the tourism sector. The type of data used in this study is time series data in 2010-2017 in the Gresik Regency area and the authors use multiple linear analysis methods, classical assumption tests, and (t) or statistical tests. The results of research conducted by this writer can be concluded that the number of tourists, the number of hotels, the number of restaurants, and the total income of the tourism sector have a positive effect on regional original income in Gresik Regency. This causes researchers to encourage local governments and tourism object managers to continue to carry out promotions and improve the facilities and infrastructure sector in order to attract tourists and tourists to feel safe and comfortable. Keywords : Number of Tourists, Number of Hotels, Number of Restaurants, Total Tourism Sector Revenue Regional Own Revenue